Research Advances in Traditional Chinese Medicine Treatment for Ischemic Stroke via Regulation of Programmed Cell Death - Liu, Litian; Chi, Liyi (Journal of Contemporary Medical Practice, 2025)
Ischemic stroke (IS) is an acute cerebrovascular event caused by cerebral vascular occlusion, leading to cerebral tissue ischaemia and hypoxia, which in turn triggers neuronal cell death and corresponding neurological deficits. Multiple forms of programmed cell death contribute to its pathological progression. Traditional Chinese medicine exerts effects through multiple pathways, targets, and levels. In recent years, an increasing number of studies have demonstrated that traditional Chinese medicine can improve stroke outcomes by regulating programmed cell death. This paper reviews relevant research with the aim of providing new insights and directions for the prevention and treatment of IS using traditional Chinese medicine.